Model dan Karakteristik Pendekatan Perencanaan Pendidikan Islam - Uskuniyah, Siti Hamidatul; Ashari, M. Yahya (Jurnal Manajemen Pendidikan Islam (MANAPI), 2024)
Islamic education planning is a strategic effort to create education that is not only oriented towards intellectual knowledge, but also towards the formation of moral and spiritual character in accordance with Islamic teachings. This article aims to examine models of Islamic education planning approaches, namely normative, pragmatic and adaptive models, as well as their main characteristics. The normative model focuses on implementing religious values consistently, the pragmatic model prioritizes relevance to current needs, and the adaptive model adapts education to the local socio-cultural context. Each model has its own advantages and challenges in creating a balance between intellectual needs and spiritual values. The main characteristics of this approach include spiritual and moral orientation, a holistic approach, and flexibility in implementation that remains based on Islamic principles. Through structured planning, Islamic education is expected to be able to form a generation that has faith, noble character, and is able to adapt to the times.